The Lamata Hillforts in the Context of the Cultural Landscape’s Transformations - Užgalis, Mantas (Archaeologia Lituana, 2018)
[full article and abstract in Lithuanian; abstract in English]The subject of this study is Lamata land hillforts in the context of transformations of cultural landscape. Before starting examine the main topic of this article there will be short summary about controversies of formation and ethnical dependencies of the microregion between Šilutė–Priekulė–Švėkšna in western Lithuania which, according to some scholars, had been existing as an ethnocultural Lamata construct in the (end of 6th?) 7th–13th centuries. The main goal of the article is to examine the influence of the paleogeographical environment and fertile and non-fertile soils for an allocation and allocation changes of the Lamata hillforts in the 1st millenium and in the beginning of the 2nd millenium AD. Finally, there is examine the functional transformations of Lamata hillforts after 13th century – the period when hillforts in Lithuania territory ceased to be used as a defensive fortifications.
Keywords: Lamata; hillforts; cultural landscape; palaeogeographical environment; soils